Integrasi Manajemen Sumber Daya Manusia dalam Pengembangan SDM Global Berbasis Human Capital dan Transformasi Digital - Vivi Riyani Magfiroh; Nailah Dwi Kirana; Arip Suhaemi; Machdum Bachtiar (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the integration of Human Resource Management (HRM) in global human resource development based on the human capital perspective and digital transformation. The study addresses the gap between classical HRM approaches and the contemporary demands of global competitiveness in the digital era. This research employs a qualitative approach through library research, utilizing content analysis and conceptual synthesis to systematically examine academic literature, including books, journal articles, and policy documents related to HRM and global human resource development. The findings reveal a conceptual integration model that connects strategic HRM, human capital development, and digital transformation within a unified framework. This model emphasizes three key dimensions: (1) strategic alignment of HRM with organizational goals, (2) continuous development of human capital through talent management and competency building, and (3) digital integration through HR analytics, e-learning, and data-driven decision-making. The study demonstrates that this integrative framework enhances cross-cultural competence, innovation capacity, and organizational adaptability in the global environment. In conclusion, the integration of strategic HRM, human capital, and digital transformation forms a systematic and adaptive theoretical framework for developing competitive global human resources in the modern era.